Sharia Compliance and Islamic Good Corporate Governance: Evidence from BMH East Java - Syakura, Abdan; Fidiana, Fidiana; Wahidahwati, Wahidahwati (Lafadz Jaya Publisher, 2025)
Zakat institutions play a strategic role in socio economic empowerment by collecting and distributing Zakat, Infaq, Sadaqah, and Waqf (ZISWAF) funds to assist underprivileged communities. This study investigates the implementation of Islamic Good Corporate Governance (IGCG) and Sharia compliance at Baitul Maal Hidayatullah (BMH) East Java, focusing on their influence on institutional performance. Adopting a qualitative descriptive approach, data were collected through semi structured in depth interviews with key stakeholders, observations, and document analysis. Findings indicate that Sharia compliance constitutes the core pillar of IGCG, ensuring transparency, accountability, and ethical fund management. Despite minor operational challenges, such as administrative hurdles for certification and variable supervisory engagement, BMH East Java demonstrates robust governance practices that reinforce public trust and improve zakat distribution efficiency. This study provides empirical evidence that IGCG serves not only as a governance framework but also as a strategic tool for enhancing credibility, operational effectiveness, and social impact, offering practical implications for zakat institutions in Indonesia.